Mechanism of spontaneous pulse shortening and a method to lengthen microwave pulse in a gigawatt relativistic BWO; IEEE International Conference on Plasma Science (ICOPS) - Mesyats G. A. Gennady Andreyevich; Korovin S. D.; Pegel I. V. Igor Valerievich; Polevin S. D.; Proskurovsky D. I. (2000, 2000)
Title screen